Effectiveness of Pandang Dengar Orang Dengan HIV Campaign in Reducing HIV Stigma among Youth in Pati Regency, Indonesia - Madona, Ade; Azizah, Adelia Nur; Nur Khasanah, Devi Jantika; Seviani, Kiky Firda; Aji, Dony Prasetyo; Arifah, Izzatul (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Recently, there has been a significant increase in new HIV infections in several regions in Indonesia, one of which is Pati Regency, Central Java. The considerable barrier in preventing HIV/AIDS is the widespread stigma against people living with HIV (PLHIV). Innovative interventions are required to eliminate HIV stigma, particularly among young people. This study evaluated the effectiveness of the Pandang Dengar Orang Dengan HIV (ODHIV) campaign in reducing HIV stigma among youth in Pati Regency, Indonesia.Methods: This was an experimental study with a pretest-posttest control group design with randomization. The residents of Pati Regency aged 15 to 29 years who were active users of Instagram and WhatsApp were involved. The Pandang Dengar ODHIV campaign was conducted using Instagram Reels four times a week for three weeks in the intervention group. The instruments used were the Global Stigma and Discrimination Indicator Working Group (GSDIWG) and the Strive research consortium. The T-test was used to analyze the data with a significance level of 95%.Results: The results revealed a decrease in HIV stigma in both the intervention and control groups (p=0.001). After the intervention, the mean stigma score in the intervention group was lower than the mean in the control group (mean difference of 0.044), however, was not statistically significant (p-value=0.961).Conclusions: The Pandang Dengar ODHIV campaign is effective in reducing HIV stigma among youth in Pati Regency, Indonesia. Further research is needed to demonstrate the effectiveness of campaign in wider audiences and other areas.